2016
DOI: 10.1002/cctc.201601120
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functional Hollow and Multihollow Organic Microspheres: Enhanced Efficiency in a Complex, Heterogeneous, Asymmetric, Three‐Component/Triple Organocascade Reaction

Abstract: The pioneered construction of monodisperse hollow and multihollow Jørgensen–Hayashi‐functionalized microspheres with a well‐defined spherical morphology, high surface area, and large pore volume were developed by initial dispersion copolymerization of the Jørgensen–Hayashi organocatalyst with acrylamide and styrene monomers cross‐linked by p‐divinylbenzene and ethylene glycol dimethacrylate, respectively, on the surface of poly(styrene/acrylic acid) (PS) microspheres to form core–shell structures, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Ma and co‐workers synthesized multihollow microspheres 256 that were functionalized with the Jørgensen–Hayashi catalyst and utilized them in an asymmetric three‐component domino Michael/Michael/aldol condensation reaction. The desired cyclohexenals 255 were obtained in excellent ee values and high diastereoselectivities (Scheme ) . The heterogeneous catalyst 256 constantly provided excellent stereoselectivities over five consecutive reaction cycles …”
Section: Primary and Secondary Amine Catalystsmentioning
confidence: 97%
“…Ma and co‐workers synthesized multihollow microspheres 256 that were functionalized with the Jørgensen–Hayashi catalyst and utilized them in an asymmetric three‐component domino Michael/Michael/aldol condensation reaction. The desired cyclohexenals 255 were obtained in excellent ee values and high diastereoselectivities (Scheme ) . The heterogeneous catalyst 256 constantly provided excellent stereoselectivities over five consecutive reaction cycles …”
Section: Primary and Secondary Amine Catalystsmentioning
confidence: 97%
“…This shell was obtained by copolymerization of acrylamide, styrene and CA6* derived monomer crosslinked with para-divinylbenzene and ethylene glycol dimethacrylate (CT15*). 163 The material was used in the tricomponent triple cascade process reported earlier, 101 View Article Online cyclohexene derivative 99. Results obtained using the heterogeneous catalyst CT15* were similar to those reported using the homogeneous counterpart CA6*.…”
Section: One-pot Reactions Using Heterogenized Chiral Organocatalystsmentioning
confidence: 99%
“…Although in DKRs enzymes are often used for the KR and heterogeneous chemical catalysts in the racemization steps, 73,75,77,[79][80][81][82] these processes are beyond the scope of the present review, as indicated in the Introduction section. An early one-pot tandem process was developed by Van Bekkum and co-workers, who combined the enzymatic isomerisation of D-glucose (161) using immobilized glucose isomerase with the heterogeneous catalytic hydrogenation of the 161 and D-fructose (162) mixture (invert sugar) to a mixture of D-glucitol (163) and D-mannitol (164). 209,210 Although the process may be considered a DKR, starting from pure 161 it was possible to reach high 164 selectivities using Cu/SiO 2 catalyst, suggesting that 161 is transformed in a biocatalytic and heterogeneous chemical catalytic cascade (Scheme 48a).…”
Section: One-pot Reactions Including Biocatalytic Asymmetric Step Commentioning
confidence: 99%
“…In the final analysis, these enhanced performances in heterogeneous organocatalysis are attributed to the improved mass transfer of reactant and product resulted from well‐controlled nano‐scale size, well‐shaped morphology of catalysts and thin trans‐mission distance of reactant. Especially in complex heterogeneous multi‐component/multi‐step organocascade reaction, these well‐controlled sizes, pores and shapes played particularly important roles in enhanced performances . An another key factor–compatibility of reactant with skeleton, also played an important role in affecting mass transfer of reactant, where hydrophobic inner surface is more favorable for the increased diffusion rate and high enrichment effect of hydrophobic reactants .…”
Section: Introductionmentioning
confidence: 99%